2013
DOI: 10.1159/000345873
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Bioartificial Pancreas

Abstract: Islet transplantation has been shown to be a viable treatment option for patients afflicted with type 1 diabetes. However, the lack of availablity of human pancreases and the need to use risky immunosuppressive drugs to prevent transplant rejection remain two major obstacles to the routine use of islet transplantation in diabetic patients. Successful development of a bioartificial pancreas using the approach of microencapsulation with perm-selective coating of islets in hydrogels for graft immunoisolation hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Tissue engineering appears to be a potential novel alternative therapy for insulin-dependent diabetes mellitus in addition to an immunosuppression-free state after transplantation, which could alleviate inevitable consequences of conventional therapies for diabetes. Islet encapsulation, which is a regenerative technology, mainly consists of packaging islet cells within a semi-permeable membrane that allows insulin, nutrients, and waste products to pass while precluding the immune response (Opara, Mirmalek-Sani, Khanna, Moya, & Brey, 2010;Vaithilingam & Tuch, 2011). Although this technique appears to obviate the requirement of immunosuppression therapy and preserve the islet cells, incompatibility of capsule material and hypoxia due to inadequate revascularization have been major obstacles in clinical studies.…”
mentioning
confidence: 99%
“…Tissue engineering appears to be a potential novel alternative therapy for insulin-dependent diabetes mellitus in addition to an immunosuppression-free state after transplantation, which could alleviate inevitable consequences of conventional therapies for diabetes. Islet encapsulation, which is a regenerative technology, mainly consists of packaging islet cells within a semi-permeable membrane that allows insulin, nutrients, and waste products to pass while precluding the immune response (Opara, Mirmalek-Sani, Khanna, Moya, & Brey, 2010;Vaithilingam & Tuch, 2011). Although this technique appears to obviate the requirement of immunosuppression therapy and preserve the islet cells, incompatibility of capsule material and hypoxia due to inadequate revascularization have been major obstacles in clinical studies.…”
mentioning
confidence: 99%
“…Studies in which alginate-encapsulated islets were transplanted into mouse models of diabetes demonstrated that glucose and insulin transport steadily increased over time, lasting anywhere from 28 days to 2-3 weeks (Pareta et al 2013, Park et al 2013. Furthermore, Park et al (2013) reported a linear relationship between the number of capsules and insulin production, providing a framework to calculate the number of capsules required to fully restore blood glucose control in animals and potentially humans.…”
Section: Bio-artificial Pancreas and Encapsulation Technologiesmentioning
confidence: 99%
“…Although alginate has some desirable attributes as a capsule material, there are additional challenges related to the need to carefully balance pore size such that cells obtain the nutrients they require while remaining completely isolated from the immune system (Pareta et al 2013, Park et al 2013. Islets require relatively high concentrations of oxygen and studies have demonstrated that hypoxia has a deleterious effect on their survival and function (Dionne et al 1993).…”
Section: Bio-artificial Pancreas and Encapsulation Technologiesmentioning
confidence: 99%
“…1 Pancreas transplantation achieves normoglycemia by reestablishing insulin release. 2,3 However, the dependence on immunosuppression and limited availability of pancreata indicate the need for other treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin injections only delay the progression of secondary complications such as retinopathy, nephropathy, and neuropathy resulting in lowering quality and expectancy of life. 1 Pancreas transplantation achieves normoglycemia by reestablishing insulin release. 2,3 However, the dependence on immunosuppression and limited availability of pancreata indicate the need for other treatment options.…”
Section: Introductionmentioning
confidence: 99%